The effect of pre- and post-emergence herbicide on weeds and rice yield in the direct seeding system - Umiyati, Uum; Kurniadie, Denny; Fauzi, Fauzi (Kultivasi, 2026)
Indonesian rice production has been unable to fully meet national demand, partly due to weed competition, which can reduce rice yields by up to 80% if left uncontrolled. This study aimed to evaluate the effectiveness of pre-emergence herbicides containing pretilachlor (300 g/L) and post-emergence herbicides containing cyhalofop + ethoxysulfuron (330 g/L) for weed control in direct-seeded rice, and  to determine the optimal dosage. Herbicides active ingredient is pretilachlor are a category of pre-emergence herbicides used in rice cultivation; these herbicides are systemic and are used to control sedges, grasses and broadleaf weeds. The cyhalofop + ethoxysulfuron herbicide is a post-emergence herbicide mixture that can suppress the growth of sedges, broad-leaved weeds and grasses . The study was conducted at PT. Syngenta Indonesia R&D Cikampek Site from August to December 2024, using a Randomized Group Design (RGD) with four replications and six treatments, namely two doses of pre-emergence herbicide (1.0 and 0.5 L/ha), two doses of post emergence herbicide (1.0 and 0.5 L/ha), manual weeding, and control (without treatment). The parameters observed included the weed vegetation analysis, dry weight of weeds, and the components of rice plant growth and yield. The results showed that pre-emergence herbicides with the active ingredient pretilachlor 300 g/L  and post-emergence herbicides with the active ingredient mixtures of cyhalofop + ethoxysulfuron 330 g/L  are effective in controlling various important weeds in the direct seeding system of rice cultivation, such as Cyperus iria, Echinochloa crus-galli, Fimbristylis miliacea, and Leptochloa chinensis, thus helping rice plants grow optimally and increasing yields. Pre-emergence herbicide with the active ingredient pretilachlor 300 g/L  at a dose of 1.0  L/ha gave the best results in suppressing weed growth and increasing rice yields compared to other treatments.